Pengaruh Efektivitas Penerapan SIA, Pemanfaatan, Kemudahan Terhadap Minat dalam Penggunaan SIA dan Kinerja Karyawan - Komang Apriadi; I Putu Julianto (Universitas Pendidikan Ganesha, 2022)
This research purpose is to study the effectiveness application of Accounting System Information (SIA), utilization of SIA, and simplicity to SIA’s user interest and effect of simplicity to SIA’s user interest to employee performance in Koperasi Dana Arta Gianyar. The population is all 53 of employee in Koperasi Dana Arta. Sample 48 respondent generated using purposive sampling method. Result shows based Multiple Regression Analysis shows that: (1) Effectiveness of SIA’s application has positive and significant effect on SIA’s user interest, (2) Utilization of SIA has positive and significant effect on SIA’s user interest, (3) Simplicity has positive and significant effect on SIA’s user interest, and (4) SIA’s user interest has positive and significant effect on employee performance. Result in simultaneously test also show that effectiveness application of SIA, utilization of SIA, and simplicity to SIA’s user interest and effect of simplicity to SIA’s user interest to employee performance.